2021
DOI: 10.2991/assehr.k.210407.226
|View full text |Cite
|
Sign up to set email alerts
|

Boomers’ Perception Towards the Implementation of Online Learning Amidst Covid-19 Outbreak

Abstract: The COVID-19 Outbreak has shifted the way education is delivered to students from conventional ways in the classroom to online interaction, requiring the use of ICT tools to assist teachers in online learning which can be a challenge for boomers as a generation who were born before the rapid development of technology. Using narrative approach, this study aimed at exploring the experiences and perceptions of eight boomer teachers who conducted online learning during this pandemic in three junior high schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The rapid changes in using technology and the frequent use of the Internet have affected the hierarchy of peoples’ needs including instructional needs and communication needs ( Trilling and Fadel, 2009 ; Diamandis and Kotler, 2012 ). Using technology in the educational system has significantly provided learners with several opportunities to act efficiently at this age ( Suwastini et al, 2020 ; Puspitasari et al, 2021 ). The existence of technological tools such as online instruction helps the students learn more flexibly and understand that traditional classrooms are not the only place to learn and teach the English language ( Dantes et al, 2019 ; Putra et al, 2020 ; Puspitasari et al, 2021 ; Utami et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid changes in using technology and the frequent use of the Internet have affected the hierarchy of peoples’ needs including instructional needs and communication needs ( Trilling and Fadel, 2009 ; Diamandis and Kotler, 2012 ). Using technology in the educational system has significantly provided learners with several opportunities to act efficiently at this age ( Suwastini et al, 2020 ; Puspitasari et al, 2021 ). The existence of technological tools such as online instruction helps the students learn more flexibly and understand that traditional classrooms are not the only place to learn and teach the English language ( Dantes et al, 2019 ; Putra et al, 2020 ; Puspitasari et al, 2021 ; Utami et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 shows that out of the 50 respondents, 30 respondents responded with "yes", 5 responded with "no", 13 responded with "partially", and the remaining 2 responded with "not at all". is implies that the majority of people believe that a computer system boosts the learning process [27]. Besides, it provides a more practical based approach to learning as well as testing the knowledge at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, study has found that, using technology encounter some challenges among baby boomer or digital immigrants, most of them stated that on line learning is hard due to lack of ICT skill, problems with internet connection, and time management. [ 31 ] Although nurse manager are digital immigrants most of them are keen to learn and researcher provided them training of how to use web and learning application. Furthermore, this INLeT model was developed for hospital.…”
Section: Discussionmentioning
confidence: 99%